Tailored pharmacist-led intervention to improve adherence to Iron supplementation in premature infants: a randomized controlled trial in China - Yu, Beimeng; Ni, Ming; Li, Haijing; Xu, Renjie; Wang, Aiping (Frontiers in Endocrinology, 2023)
Introduction: Prematurity is due to a number of factors, especially genetics. This study was designed to evaluate the impact of a pharmacist-led patient-centered medication therapy management trial on iron deficiency and medication adherence among premature infants receiving iron supplementation at a tertiary hospital in Shaoxing, China. Methods: In this randomised controlled trial, eighty-one premature infants, with or without genetic factors, born at 26 to 30 weeks and 6 days gestational age, will be recruited and randomised to an intervention group or a control group. The intervention group will receive a pharmacist-driven discharge counseling on iron supplements from recruitment, until 12 months. The control group will receive care as usual. The main outcomes were haemoglobin (g/L), serum iron (μg/L), medication adherence estimation and differentiation scale, the satisfaction with information about medicines scale, beliefs about medicines questionnaire and the Bayley scales for infant development.Results: A total of 81 patients were enrolled in the study. After intervention, results for the haemoglobin and serum iron differed significantly between the control group and the intervention group (101.36 vs. 113.55, P < 0.0001 and 51.13 vs. 101.36, P = 0.004). Additionally, there was a substantial difference between the intervention group and the control group in terms of patient medication adherence estimation and differentiation scale (27 vs. 34, P = 0.0002). the intervention group had better mental This is a provisional file, not the final typeset article development index and psychomotor development index, compared with the control group (91.03 vs. 87.29, P = 0.035 and 95.05 vs. 90.00, P = 0.022).Discussion: In premature infants with iron deficiency, our pharmacist-led team significantly improved clinical outcomes and medication adherence.